Composite material characterisation using an advanced small angle x-ray (SAXS) technique - Yazid H.; Murshidi J.A.; Jamro R.; Megat Harun M.A.; Mohamed A.A. (Institute of Physics Publishing, 2023)
Agglomeration; Alumina; Composite materials; Fillers; X rays; Characterization techniques; Degree of agglomeration; Material characterisation; Materials development; Scattering pattern; Scattering techniques; Small-angle x-rays; Thermoplastic natural rubbers; Characterization